The element of art - Cichoń, Krzysztof; Kuczyńska, Agnieszka (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
The article juxtaposes the feeling of the rationally uncontrolled spontaneity of art with the concept of a sketch as a reaction method. Methods of spontaneous (reflexive, unconscious, instinctive?) action towards what is incomprehensible, illegible, and at the same time treated as potentially existentially important. This is very often an area of instant associations. Associations focused on a quick reaction, not on long, rational analysis. In this context, one of the fundamental problems of today’s “art sciences” is the administrative prohibition of sketchily treating things as (existentially) important for science as points for publications.